GAMBARAN PENGETAHUAN DAN SIKAP TERHADAP EDUKASI JAJANAN SEHAT DAN GIZI SEIMBANG PADA SISWA KELAS V DI SDN 064975 MEDAN DENAI - Suci Rahmadani (CV. Adiba Aisha Amira, 2024)
Food or snacks are topics that must be of public concern. Structuring nutrition or child nutrition in the growth and development phase does not always succeed until the end, because problems often arise such as the rampant use of harmful substances in food, children's behavior of consuming harmful snacks, lack of parental supervision of children's snack behavior. The goal of this study was to gather data on the opinions of SDN 064975 grade V pupils on nutritious snacks and a balanced diet. Cross-sectional observational studies and quantitative research are the study methods used. A questionnaire that was completed by the sample at the time of the pretest and posttest served as the method of data collection in this investigation. Primary data and secondary data are the two categories of data used in this study. Observations at SDN 064975 Medan Denai revealed that a lot of refreshments were sold all around the school. Fried dishes, balado chips, egg rolls, colored ice, and other munchies are examples of this. Physically, it is evident that the food is harmful since it contains ingredients that aren't healthy.. The conclusion of this study is that there is a significant diflerence between knowledge value (p- value 0.034 danlt; 0.05) and attitude (p-value 0.000 danlt; 0.05) before and after learning healthy snacks and balanced nutrition in knowledge training and attitudes of grade V students.